Ethical formation and ethical dilemmas - Iracheta Fernández, Francisco Javier (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
In this paper, I want to analyze the meaning of the practice of training college students in ethics to prepare them for solving «ethical dilemmas». Starting from the proposal that has been made by UNESCO to integrate ethical education in the curricula of professional studies, my aim is to show the sense that acquires the concept of ethical dilemma and the significance that this concept implies, once we accept its legitimacy, for the teaching of Ethics, and from this, to invite the reader to reflect upon the type of pedagogy of Ethics that one, as a professional ethics instructor, must put into action for teaching future professionals to attend ethical dilemmas related with their lives and professional activities.
Keywords: ethical dilemmas; ethical upbringing; professional education; moral health; therapeutically scope